Data for 'Extremely low surface recombination in 1 Ωcm n-type monocrystalline silicon' - Bonilla, R; Wilshaw, P (University of Oxford, 2016)
Data set embedded in Matlab figures representing the conductance-voltage spectra and interface state density (Dit) derived from it, effective lifetime (tau_eff) as a function minority carrier (Delta_n) and Surface potential, and surface recombination velocity and current calculated from lifetime data, as a function of injection level.